Economic impact assessment of small-scale sporting events using Social Accounting Matrices: an application to the Spanish Football League. Issue 3 (2nd September 2017) - Amador, L.; Campoy-Muñoz, P.; Cardenete, M. A.; Delgado, M. C.
ABSTRACT: Small-scale sporting events contribute to hosting economies through the expenditures of both sports team activities and sports tourism. Among these sports, football has an increasing importance worldwide, with outstanding competition, such as the Spanish Football League. The goal of this paper was to assess the impact of a team's promotion on the hosting economy by using linear models based on regionalized Social Accounting Matrices (SAMs). The proposed methodology is applied to the real case of the promotion of the Spanish team Cordoba F.C. over the 2014–2015 season. Estimates are made under two scenarios, conservative and progressive, encompassing different rates of both attendance and average expenditure per spectator and per match. The results highlight that the net expenditures associated with small-scale sporting events benefit the hosting economy, spurring the production of goods and services directly demanded as well as the production of supplier activities.